PENINGKATAN KEMAMPUAN MENULIS PENGLAMAN PRIBADI DENGAN MENGGUNAKAN MODEL INVESTIGASI KELOMPOK SISWA KELAS VIII MTS AL-KHAIRAAT GURAPING OBA UTARA - Justam Wahab (Universitas Khairun, 2021)
The problems in this study were (1) whether the improvement of writing skills in personal experiences using the group investigation model of class VIII MTs students. Al-Khairaat Guraping the northern oba? (2) How to increase the ability to write personal experiences using the group investigation model of class VIII students at MTs Al-Khairaat Guraping Oba utara? The research was conducted with the aim of (1) To determine the results of the use of the group investigation model in learning to write personal experiences in class VIII students of MTs. Al-Khairaat Guraping northern oba. (2) To determine the increase in the ability to write personal experiences using the group investigation model of class VIII MTs students. Al-Khairaat Guraping northern oba. The method used in this research is quantitative descriptive. The population in this study were 70 students of class VIII MTs. Alkhairaat Guraping northern oba. While the sample in this study was 30 students at 50%. Based on the results of the analysis and conclusions, it can be seen (1) observations of teachers in the field of Indonesian studies that have implemented the teaching and learning process properly in accordance with the application of the curriculum and the use of learning tools in the form of syllabus and lesson plans in writing personal experiences;; (2) the initial test (pretest) of students who get very good qualifications (SB) are 6 by 20%, students who get good qualifications (B) are 26%, students who get quite good qualifications (CB) are 8 by 26 %, students who get poor qualifications (KB) as many as 5 as many as 16. Have not achieved an increase; (4) students who get very good qualifications (SB) are 14 by 46%, students who get good qualifications (B) are 23%, students who get quite good qualifications (CB) are 9 by 30 %, students who get poor qualifications (KB) as many as 0 students by 0% achieve an increase.